Parental Involvement in Supporting Academic Performance of Intermediate Phase Learners in a Low Socio-Economic Context - Tumelo Mekgwe; Nonhlanhla Maseko; Mabatho Sedibe (Indonesia Approach Education, 2024)
Parental involvement is essential for realising quality school performance and good academic performance. The study explores the role of parents’ involvement in intermediate-phase learners’ academic performance in a low socio-economic context in the North West Province, South Africa. This study intended to assist schools with strategies that could be used by the schools to involve parents to enhance the academic performance of learners. The study followed a qualitative design, underpinned by the interpretivism paradigm to explore the role of parental involvement in supporting intermediate-phase learners academically. Data was gathered using semi-structured individual and focus group interviews, and document analysis. Three parents were purposively selected to participate, from each grade (Grades 4,5,6). Thus, the total number of participating parents was nine, comprising six females and three males. The article is underpinned by the Epstein model of school, family, and community partnership that encourages mutual collaboration between different stakeholders. The findings indicated that parental involvement in children’s education enhances their academic performance.